Prognostic value of remnant cholesterol in patients with coronary heart disease: A systematic review and meta-analysis of cohort studies - Tian, Yun; Wu, Wenli; Qin, Li; Yu, Xiuqiong; Cai, Lin; Wang, Han; Zhang, Zhen (Frontiers in Cardiovascular Medicine, 2023)
Background The relationship between abnormal lipid levels and atherosclerotic cardiovascular diseases is well established, but the association between remnant cholesterol (RC) and coronary heart disease (CHD) remains uncertain. The aim of this meta-analysis is to systematically evaluate the prognostic value of RC concentration in patients with CHD. Methods PubMed, EMBASE, Cochrane, and Web of Science databases were reviewed to identify relevant observational cohort studies published in English up to December 2021. Random-effects meta-analysis compared the highest and lowest RC concentration. The primary outcome was a composite of major adverse cardiovascular events (MACEs) and all-cause mortality in patients with CHD. Results A total of 10 studies recruiting 30,605 patients with CHD were selected to be included in this meta-analysis. Patients with CHD with elevated RC concentration had an increased risk of the composite endpoint events (RR = 1.54, 95% CI: 1.26–1.87) and MACEs (RR = 1.70, 95% CI: 1.54–1.88), but the risk of all-cause mortality was not statistically significant (RR = 1.16, 95% CI: 0.79–1.69, P = 0.44). Subgroup analysis showed consistent results. Conclusion Our results suggest that elevated concentration RC may independently predict MACEs in patients with CHD. Determination of RC concentration may improve risk stratification of prognosis in patients with CHD. However, more high-quality studies are necessary to confirm this association.